A Distal Radial Metaphyseal Stress Fracture in an 11-Year-Old Capoeira Dancer: A Case Report. Issue 4 (December 2016) - Keren, Timoret
Stress fractures are commonly an overuse injury. They result from recurring mechanical loads imposed on abone causing an imbalance between bone resorption and remodeling. The damage ultimately weakens the bone structure resulting in microfractures that cause pain, swelling, and disability. Capoeira is a martial art, also classified as a dance, which is very popular as a recreational activity among school children and young adults. It incorporates quick and complex movements that use the hands and wrists repeatedly to balance the weight of the body, as in a handstand or a cartwheel. An 11-year-old recreational Capoeira dancer presented to the clinic with left wrist pain that had been bothering him for 3 months. The clinical investigation and imaging results revealed a stress fracture in the distal radius metaphysis. It was concluded that the pattern of repetitive stress to the wrist typical of Capoeira movements caused a stress fracture to appear in this unusual location.